Analyzing the Relationship between Coping Strategies and Functioning Levels of Patients with Bipolar Disorder - Şahin Altun, Özlem; Durmuş, Mustafa; Öztürk, Zeynep (Ataturk Universitesi, 2024)
Objective: The study aims to determine the relationship between coping strategies and functioning levels of patients with bipolar disorder. Methods: This study is a descriptive and correlational study. The study was conducted with patients diagnosed with bipolar disorder who presented to the psychiatry outpatient clinic of a hospital in the Eastern Anatolia Region between March 2017 and January 2018. Results: A significant positive relationship was found between the mean FAST score and “focus on and venting of emotions,” “substance use,” “acceptance,” “suppression of competing activities,” “turning to religion,” “denial,” “behavioral disengagement,” “positive reinterpretation,” “using emotional social support,” and “planning”, which are the sub-scales of the CSS-BF. Conclusion: The coping strategies used by the patients were found to be effective in their functioning levels. © 2024, Ataturk Universitesi. All rights reserved.
Bipolar Bozukluk Tanısı Alan Hastaların Başa Çıkma Stratejileri ile İşlevsellik Düzeyleri Arasındaki İlişkinin İncelenmesi
Keywords: Bipolar disorder; coping; functioning; nursing